Implikatur dalam Komik Yotsuba&! Vol. 1-3 Karya Kiyohiko Azuma - Putri, Mirda Adzka (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2022)
This research is a study of the implicatures in the Yotsuba&!, a comic book by Kiyohiko Azuma on the volume 1-3. The purpose of this study is to describe the violation of maxims that occur in implicature utterances and classify the types of implicatures found based on the cooperative principle theory proposed by Grice (1975) and the classification of implicatures according to Yule (2014). The data were analyzed by using a qualitative descriptive method. As a result of the study it is found that there are as many as 20 violation of maxims data and 24 implicature data.